2021
DOI: 10.7759/cureus.19398
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diabetes Mellitus in Heart Failure With Preserved Ejection Fraction: A Review Article

Abstract: The pathophysiology of heart failure with preserved ejection fraction (HFpEF) is complex and poorly understood. There is a high prevalence of Diabetes Mellitus (DM) in patients with HFpEF, and the presence of DM has been shown to increase mortality of patients with HFpEF by 30%-50% even after adjustment for age, gender, hospital factors, and other patient characteristics. Since the prevalence of both entities is increasing worldwide, there is a need to explore their intricate relationship in order to elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Unlike HF with reduced ejection fraction (HFrEF), HFpEF has distinct clinical phenotypes, and the obese-diabetic phenotype is the most often encountered phenotype in clinical practice. 38,39 In the Phosphodiesterase-5 inhibition to improve clinical status and Exercise capacity in Diastolic HF (RELAX) trial, 40 body mass index (BMI) was 37.1 vs. 30.7 kg/m 2 in patients with and without T2DM. In this category of patients, LV remodelling was more relevant and associated with reduced ventricular compliance with increased systemic and pulmonary venous pressures and congestion despite preserved systolic function.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike HF with reduced ejection fraction (HFrEF), HFpEF has distinct clinical phenotypes, and the obese-diabetic phenotype is the most often encountered phenotype in clinical practice. 38,39 In the Phosphodiesterase-5 inhibition to improve clinical status and Exercise capacity in Diastolic HF (RELAX) trial, 40 body mass index (BMI) was 37.1 vs. 30.7 kg/m 2 in patients with and without T2DM. In this category of patients, LV remodelling was more relevant and associated with reduced ventricular compliance with increased systemic and pulmonary venous pressures and congestion despite preserved systolic function.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…There is a high prevalence of T2DM in patients with HFpEF, and the presence of T2DM has been shown to increase mortality of patients with HFpEF by 30–50% even after adjustment for age, gender, hospital factors, and other patient characteristics. Unlike HF with reduced ejection fraction (HFrEF), HFpEF has distinct clinical phenotypes, and the obese–diabetic phenotype is the most often encountered phenotype in clinical practice 38,39 …”
Section: Background: Role Of Obesity In Heart Failure With Preserved ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although diabetes appears to have a well-established role in HFpEF development, less is known regarding its impact on established HFpEF. Notably, while metformin has been reported to improve HFpEF outcomes (Wang et al, 2021), none of the other anti-diabetes medications have been shown to confer survival benefits (Mgbemena et al, 2021) except for SGLT2 inhibitors (whose cardioprotective effect is likely independent of its anti-glycemic function (Anker et al, 2021;Ebell, 2022)). Thus, these observations support diabetes as a risk factor for HFpEF development but challenge the notion that diabetes continues to play an active role in established HFpEF.…”
Section: Obesity and Diabetesmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is one of the most frequently seen risk factors and comorbidities in patients with congestive heart failure (CHF) ( 11 , 12 ), and it adversely affects outcomes in these patients ( 13 , 14 ). The impact of T2DM on different phenotypic presentations of HF, especially in patients with HF and preserved ejection fraction (HFpEF), remains unclear ( 15 , 16 ). Impaired energy metabolism and muscle fiber-type switches ( 17 , 18 ) found in T2DM, similar to what is seen in CHF, have been previously shown.…”
Section: Introductionmentioning
confidence: 99%